One-pot synthesis of substituted pyrrolo[3,4-b]pyridine-4,5-diones based on the reaction of N-(1-(4-hydroxy-6-methyl-2-oxo-2H-pyran-3-yl)-2-oxo-2-arylethyl)acetamide with amines - Valeriya G. Melekhina (Beilstein Journal of Organic Chemistry, 2019)
The condensation of primary amines with N-(1-(4-hydroxy-6-methyl-2-oxo-2H-pyran-3-yl)-2-oxo-2-arylethyl)acetamides was explored. Thus, a previously unknown recyclization of the starting material was observed in acidic ethanol in the presence of an amine, which provided the corresponding dihydropyrrolone derivative as the major reaction product. Based on this transformation, a practical and convenient one-pot synthetic method for substituted pyrrolo[3,4-b]pyridin-5-ones could be devised.